Perivascular adipose tissue as an endocrine organ: the role of statins - Sanna, F; Margaritis, M; Antoniades, C (Bentham Science Publishers, 2017)
Adipose tissue (AT), aside from being an energy storage site, functions as a source of cytokines, adipokines and other vasoactive molecules. Dysfunctional AT contributes to the development of cardiovascular disease by shifting to a pro-oxidant, pro-inflammatory phenotype. Perivascular AT (PVAT) is of particular importance to the development of vascular disease, due to its close proximity to the vascular wall. Molecules released from PVAT can exert both pro- and anti-contractile effects, the balance of which plays a role in controlling vascular tone. Recent evidence supports the existence of reciprocal, two-way interactions between PVAT and the vascular wall. Statins, with their pivotal role in cardiovascular disease prevention, have been shown to exert lipid-lowering independent, pleiotropic effects on the vascular wall, some of which may be mediated by modulatory effects on PVAT inflammation and secretome. These effects of statins provide a paradigm for the development of new therapeutic agents aimed at modulating PVAT function, as a novel treatment strategy against cardiovascular disease.